A visegrádi országok és a 2008-as válság - Botos, Katalin; Nógrádi, Tamás (Közép-Európai Közlemények, 2015)
Due to their geographical location and historical baackground, the countries of Visegrád offer a great opportunity of comparing their economic indices and their decisions regarding economic policies. The decade of post$socialist transition followed by a relatively favourable economic environment shows dissimilar tendencies in terms of certain macroeconomic indices. The employment, the incurring debts of the state and the private sector, and the data regarding the level of redistribution of the state all appear in the economy's power, in which Hungary’s fallback is clearly observable. The high level of external and internal national debt and the effect of spending on the consumption of the private sector passed soon, and made Hungary vulnerable to external shocks. Naturally, the aforementioned facts influenced the possible answers given to the crisis of 2008, the applicable fiscal and monetary political instruments and it is constricting the originally narrow margin of the economic policies up to this day.